Indonesia, modernity and some problems of religious adaptation - McDaniel, June (Wacana, Journal of the Humanities of Indonesia, 2014)
This article discusses the challenges of adaptation for Indonesian religion. It describes the ways that the major Indonesian religions have changed to fit the requirements of being recognized religions, and focuses as an example on the ways that Balinese Hinduism has changed to become Agama Hindu Dharma Indonesia. It also examines the traditional theological problem of "faith and works" in the Indonesian context, and the concerns used to balance modernization and religious freedom.